Mitochondrial DNA and traumatic brain injury. Issue 2 (1st March 2014) - Bulstrode, Harry; Nicoll, James A. R.; Hudson, Gavin; Chinnery, Patrick F.; Di Pietro, Valentina; Belli, Antonio
<x xml:space="preserve">Abstract</x> Objective Traumatic brain injury (TBI) is a multifactorial pathology with great interindividual variability in response to injury and outcome. Mitochondria contain their own DNA (mtDNA) with genomic variants that have different physiological and pathological characteristics, including susceptibility to neurodegeneration. Given the central role of mitochondria in the pathophysiology of neurological injury, we hypothesized that its genomic variants may account for the variability in outcome following TBI. Methods We undertook an analysis of mitochondrial haplogroups in a large, well‐characterized cohort of 1, 094 TBI patients. A proportional odds model including age, brain computed tomography characteristics, injury severity, pupillary reactivity, mitochondrial haplogroups, and APOE was applied to Glasgow Outcome Score (GOS) data. Results mtDNA had a significant association with 6‐month GOS (p = 0.008). Haplogroup K was significantly associated with favorable outcome (odds ratio = 1.64, 95% confidence interval = 1.08–2.51, p = 0.02). There was also a significant interaction between mitochondrial genome and age (p = 0.002), with a strong protective effect of both haplogroups T (p = 0.015) and K (p = 0.017) with advancing age. We also found a strong interaction between APOE and mitochondrial haplogroups (p = 0.001), indicating a protective effect of haplogroup K in carriers of the APOE ε4 allele. Interpretation These findings reveal an interplay between mitochondrial DNA, pathophysiology of TBI, and aging. Haplogroups K and T, which share a common maternal ancestor, are shown as protective in TBI. The data also suggest that the APOE pathways interact with genetically regulated mitochondrial functions in the response to acute injury, as previously reported in Alzheimer disease. Ann Neurol 2014;75:186–195